The effect of supporter exercise similar of the performance of the elevation of lying down pushing (Bench Press) in the relative strength of the muscles of the arms of a sample of players power strength - Qusi, Mohammed (Journal of Physical Education, 2014)
The research aims to identify the impact of assistance exercise similar to the performance of the bench press in the arm’s strength relative of a sample of player’s power lifting and was a research sample is composed of a team Club Sedea sports power lifting within the weights legal sport’s power lifting where the sample was divided into two groups and are random , after selecting test of research and conduct assistance exercise the experimental group researcher found several results was the most important: influenced assistance exercise in a positive way to the experimental group, where the results were significantly between tests before and after and in favor of the dimensional ratios of evolution with the experimental group is higher than the control group, where the ratio of the experimental (17 %), while the control group was (7). The results were randomized between posttest for the control and experimental groups at maximum power (the relative strength of the arms)